Analisis Passing dan Shooting pada Final Piala Super Spanyol Antara Real Madrid VS Barcelona 2025 - Waluyo Kridho Asmoro; Abdul Aziz Hakim; Mokh. Nur Bawono; Afif Rusdiawan (Mutiara Pendidikan dan Olahraga, 2025)
Football players must be proficient in passing and shooting techniques to play the game on the field. Real Madrid and Barcelona have good passing and shooting skills and have interesting game characteristics. This study analyzes the passing and shooting technique skills of players in the El Classico Final of the 2025 Spanish Super Cup, using quantitative research methods with a descriptive approach. Real Madrid gained 321 successful and 60 unsuccessful. Meanwhile, in the Barcelona team, the number of passing players is 376 who succeed and 57 who fail. Meanwhile, in the long pass, Real Madrid won 30 successful and 35 unsuccessful. The Barcelona team obtained 26 successes and 32 failures. Real Madrid's ball possession got an Instep shoot 1 on goal, 4 on target, 13 off target and 1 free kick on goal. Meanwhile, Barcelona got an Instep shoot of 5 on goal, 3 on target, 6 off target. Barcelona's passing and shooting ability tends to be better than Real Madrid's. This proves that many passing and shooting affect the score or the entry of the ball towards the goal.